Dual-key cooperatively activated DNA regulator for controlling mitochondria-lysosome interactions - Yang Xiao; Longyi Zhu; Songyuan Du; Xinyi Ge; Lequn Ma; Shengyuan Deng; Kewei Ren (Nature Communications)
Abstract Mitochondria-lysosome interactions are critical for maintaining cellular homeostasis. Although genetically encoded protein based optogenetic technique is developed to regulate such interactions, it still suffers from shortcomings including complicated operation and potential interference to organelle functions. Here, we present a fast, simple, biocompatible and programmable platform via activable DNA regulators to achieve spatiotemporal regulation of mitochondria-lysosome interactions in living cells. In our system, two locked DNA regulators, OK-MLIR and DK-MLIR, that can be respectively activated with UV light (One Key) as well as UV light and endogenous glutathione (Dual Keys), are modularly designed for modulating mitochondria-lysosome contacts. We show that these DNA regulators can be used for facilitating mitochondrial fission and autophagy. Moreover, the DK-MLIR enables selective and efficient manipulation of target cell migration and proliferation with highly temporal and spatial controllability. This programmable and modular design principle provides a platform for organelle interaction study, cellular regulation and precision therapy.